Middle Ear Cavity and Mastoid Neuroendocrine Tumor Presenting as Otomastoiditis with Cholesteatoma: A Clinicoradiological and Histopathological Correlation - Chalikandy, Ashwini; Basu, Sandip (World Journal of Nuclear Medicine, 2023)
Neuroendocrine tumors of the middle ear are rare, comprising of less than 2% of primary tumors of the ear. The clinical and imaging findings of these tumors are nonspecific, and histological and immunohistochemical findings are confirmatory. Herein, we present a case of 48-year-old male, presenting with chief complaints of hearing loss of left ear with foul smelling discharge, with the initial clinical impression of otomastoiditis of the middle ear with cholesteatoma and being operated for the same, the final histopathology report inferred it as well-differentiated neuroendocrine tumor grade 1 with Ki-67 index less than 2%. Immunohistochemical examinations demonstrated positive staining of the tumor cells for cytokeratin, synaptophysin and chromogranin A, and negative for smooth muscle actin, desmin, S-100. The biochemical investigations showed raised serum chromogranin A levels. Based upon the findings on anatomical imaging modalities including high-resolution computed tomography temporal bone and magnetic resonance imaging paranasal sinuses (MRI PNS), the lesion was inferred inoperable due to involvement of dura of petrous apex, and therefore he was referred for consideration of peptide receptor radionuclide therapy (PRRT). MRI PNS also showed involvement of the horizontal part of facial nerve, indicating local aggressiveness of the tumor. 68Ga-DOTATATE-PET/CT showed high-grade somatostatin receptor expressing soft tissue lesion involving middle ear and external auditory canal (Krenning's score 4), with low-grade metabolic activity on 18F-FDG-PET/CT. The post-therapy scan following 177Lu-DOTATATE PRRT, showed abnormal tracer concentration at the described site. Due to extreme rarity of this disease entity, it is important to accrue data for accurate diagnosis, proper management, and follow-up.
Keywords: neuroendocrine tumor; middle ear cavity; 68Ga-DOTATATE-PET/CT; 177Lu-DOTATATE PRRT